PENINGKATAN KEMAMPUAM MEMBACA PEMAHAMAN DENGAN TEKNIK CLOZE TEST PADA SISWA KELAS VIII G SMP NEGERI 2 GANTIWARNO KLATEN TAHUN AJARAN 2015/2016 - Wiji Santoso; Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2016)
This research has purposed to describe (1) the increase in the activity of reading students with Cloze test technique and, (2) improvement of reading skills of students with Cloze test technique in class VIII G SMP 2 Gantiwarno Klaten. The subject were students of class totaling 33 students and the object of this study is the process of learning reading skills to find the main idea with Cloze test technique. Data collection methods used in the study was the observation, test, interview, and documentation. The validity of the data with content validity and reliability inter-rater. The result showed that, (1) an increase in students reading activity increases, namely in prasiklus amounted to 54,54%, the first cycle of 63,63and 84,84% second cycle becomes. (2) improvement of students reading ability increases, namely in prasiklus amounted to 68,68%, the first cycle of 72,22%, and the second cycle into 76,76%.